A comprehensive review on heat transfer and pressure drop characteristics and correlations with supercritical CO2 under heating and cooling applications. (September 2018) - Ehsan, M. Monjurul; Guan, Zhiqiang; Klimenko, A.Y.
Abstract: The CO2 with superior thermo-physical properties has numerous applications in nuclear reactor, power plant, refrigeration and air conditioning systems as well as in many engineering and industrial applications. The complex phenomenon of thermal and hydrodynamic behaviour associated with supercritical CO2 is a continuing research topic for many researchers. The conventional correlations of turbulent forced convection heat transfer failed to predict the heat transfer and flow behaviour especially in the vicinity of the critical condition. The present paper presents a comprehensive review of heat transfer characteristics and correlations with supercritical CO2 employed under heating and cooling condition in horizontal channel or tube. An exhaustive review of implementation of supercritical CO2 used with horizontal and vertical orientation of tubes under turbulent flow condition and other operating parameters (inlet sCO2 pressure, mass flux, temperature, and heat flux) is also reported. In the present work, possible reasons for heat transfer deterioration under heating of supercritical CO2 are discussed. The characteristics of pressure drop, convective heat transfer behaviour, effect of buoyancy, the wall temperature distribution and finally the comparison among different correlations are reviewed extensively for supercritical CO2 . The study of these correlations with their range of applicability provides a good insight for efficient thermal design and optimization of heat exchanger especially in thermal power plants. Highlights: Review of heat transfer correlations for supercritical CO2 in horizontal tubes. Review of experimental and numerical works in different flow configurations. Influence of operating conditions on heat transfer mechanism and flow behaviour. Physical reasoning on the variation of correlations with experimental dataset. Heat transfer deterioration of supercritical CO2 under heating application.